Seroprevalence and risk factors associated with toxoplasmosis in nomadic, rural, and urban communities of northwestern Iran - Bahadori, Ali; Babazadeh, Towhid; Chollou, Khalil Maleki; Moqadam, Hanane; Zendeh, Mostafa Bafandeh; Valipour, Behnaz; Valizadeh, Leili; Valizadeh, Soghra; Abolhasani, Sakhavat; Behniafar, Hamed (Frontiers in Public Health, 2025)
ObjectivesToxoplasmosis is an infection that is widespread in populations comprising humans and other warm-blooded creatures and is caused by the protozoan parasite called Toxoplasma gondii. Hence, knowledge of seroprevalence and associated risk factors is essential for planning adequate and efficient population health interventions. The objective of the present study was to evaluate the seropositivity of T. gondii infection and to study the epidemiological indices in different categories of populations in East Azerbaijan Province, Iran.MethodsThis cross-sectional survey involved 426 participants 10 years of age and older from urban, rural, and nomadic areas. Serum samples were collected and analyzed for IgG antibodies against T. gondii using the ELISA method. Demographic data, such as age, occupation, soil contact, and cat ownership, were collected through questionnaires.ResultsThe overall prevalence of toxoplasmosis was 62.2%, and a significant relationship between the infection and age, exposure to soil, and job involvement was observed. Farmers and ranchers had the highest occurrence rate of 69.4%; no association of the prevalence with gender, education, income, cat ownership, or eating habits was observed.ConclusionOccupational risk factors appear to play a significant role in the transmission of toxoplasmosis, although there is doubt cast on classic risk factors such as cat handling and ingesting contaminated foodstuffs. Such exposure can lead to risky transmission of T. gondii; therefore, continued surveillance and specific approaches in public health are needed to address such risks in the area.